Pelatihan Aplikasi Canva Desain dalam Pembuatan Konten Marketing - Subagja, Ghia; Damayanti; Aprilia, Hani Damayanti (Jurnal Pengabdian Dharma Wacana, 2024)
The purpose of this service is to provide skills to novice entrepreneurs in utilizing the Canva Design application in creating marketing content. The method used is by training and practice. Training evaluation includes indicators: (1) Participants’ understanding of the material provided based on the results of participants’ pre-test and post-test evaluations; (2) Enthusiasm/response of participants in participating in activities; (3) Participants’ ability in practice; (4) Clarity of speakers in delivering material. The long-term target that will be achieved in this activity is to make skilled novice entrepreneurs to utilize the Canva Design application in creating marketing content. Overall, the average score of participants before the socialization activity was 38.57 and increased to 86.43 after the training activity. The average increase was 47.86 points. The highest pre-test score is 50 and the lowest value is 20, while for the posttest session the highest score is 100 and the lowest value is 70. Based on these results, it can be concluded that this service activity is able to have a cognitively positive impact on knowledge about the use of the Canva Design application in creating marketing content. Meanwhile, from the affective side, awareness, willingness, and ability of participants in applying the use of the Canva Design application in creating marketing content.